2012
DOI: 10.1038/bjc.2011.588
|View full text |Cite
|
Sign up to set email alerts
|

Detection of gastric cancer-associated microRNAs on microRNA microarray comparing pre- and post-operative plasma

Abstract: Background:Recently, it was reported that plasma microRNAs (miRNAs) are low-invasive useful biomarkers for cancer. We attempted to isolate gastric cancer (GC)-associated miRNAs comparing pre- and post-operative paired plasma, thereby excluding the possible effects of individual variability.Methods:This study was divided into four steps: (1) microarray analysis comparing pre- and post-operative plasma; (2) validation of candidate miRNAs by quantitative RT–PCR; (3) validation study of selected miRNAs using paire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
148
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(155 citation statements)
references
References 38 publications
6
148
1
Order By: Relevance
“…This is especially the case in Asia, with the highest incidence being found in China, Japan, and Korea (Ferlay et al, 2010;Saeki et al, 2013), and about 1,000,000 new cases every year (Yang, 2006). There is increased expression of miR-421, miR-21, miR-221/222, and miR-106a in gastric cancer, while the expression of miR-124a, miR-128b, miR-148, and miR-129 is reduced (Guo et al, 2009;Konishi et al, 2012). MiRNA-21 was one of the first miRNAs to be discovered in human cells, and its expression is significantly upregulated in different kinds of solid tumors, for instance breast and gastric cancer, and is closely associated with cancer pathogenesis (Huang et al, 2013).…”
Section: Macrophage-secreted Exosomes Delivering Mirna-21 Inhibitor Cmentioning
confidence: 99%
“…This is especially the case in Asia, with the highest incidence being found in China, Japan, and Korea (Ferlay et al, 2010;Saeki et al, 2013), and about 1,000,000 new cases every year (Yang, 2006). There is increased expression of miR-421, miR-21, miR-221/222, and miR-106a in gastric cancer, while the expression of miR-124a, miR-128b, miR-148, and miR-129 is reduced (Guo et al, 2009;Konishi et al, 2012). MiRNA-21 was one of the first miRNAs to be discovered in human cells, and its expression is significantly upregulated in different kinds of solid tumors, for instance breast and gastric cancer, and is closely associated with cancer pathogenesis (Huang et al, 2013).…”
Section: Macrophage-secreted Exosomes Delivering Mirna-21 Inhibitor Cmentioning
confidence: 99%
“…Various miRNAs are differentially expressed in gastric cancer cells. miR-421, miR-21, miR-221/222, and miR-106a show increased expression in gastric cancer, while miR-124a, miR-128b, miR-148, and miR-129 show decreases in expression (Guo et al, 2009;Konishi et al, 2012). miR-421 target genes are down-regulated via miR-421 binding to the 3'UTR of ATM (Hu et al, 2010).…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, compared to serum, plasma might retain higher protein levels, including those of coagulant-related proteins. These finding prompt us to consistently use plasma miRNAs in future clinical application [25,[34][35][36][37][38][39][40][41][42][43][44]. Indeed, miRNA profiles and miRNA concentrations were considerably different between serum and plasma.…”
Section: Discussionmentioning
confidence: 99%
“…We limited the target miRNAs to oncogenic miRNAs, as previous studies have revealed that high plasma levels of oncogenic miRNAs might be derived from tumor necrosis, apoptosis and the active release of secretory vesicles, such as exosomes, from cancer cells; thus, these miRNAs in plasma could reflect tumor dynamics in cancer tissues [34][35][40][41]. Tumorsuppressive miRNAs and functionally unknown miRNAs were excluded in the present study because the origin of these miRNAs is not well known [38]. Consequently, 48 miRNAs were excluded.…”
Section: Selection Of Candidate Mirnas From the Ncbi Databasementioning
confidence: 99%
See 1 more Smart Citation